THE RELATIONSHIP OF THE FAMILY OF LANGUAGE IN EAST BARITO, CENTRAL KALIMANTAN (DAYAK MAANYAN AND DAYAK DUSUN) - Pitaloka, Sonia; Wianie, Ramyola Arisha; Rachmiati, Desy; Mardina, Tiara; Utami, Lusi Tri; Misrita, Misrita (Journal Compound: Improving the Quality of English Education, 2023)
This study explored the linguistic relationship between the Dayak Maanyan and Dayak Dusun languages in the East Barito region of Central Kalimantan. Focusing on lexical and phonological features, the research employed a descriptive qualitative approach to analyze 200 glosses from both languages, systematically selected based on the Swadesh list. The glosses were categorized into parts of speech, including nouns, pronouns, verbs, adverbs, adjectives, prepositions, and conjunctions. These glosses were compared to identify similarities and differences. The findings indicated substantial overlap in linguistic structures, reflecting a shared Austronesian heritage, while also revealing distinct variations shaped by cultural and geographical influences. These differences highlighted the dynamic evolution of languages within the same region, driven by social interactions and environmental adaptations. This research provided valuable insights into the linguistic diversity and convergence within the East Barito language family, contributing to the broader understanding of indigenous languages in Central Kalimantan.